Konflik Sosial Dalam Film Alephia 2053 - Dinanti, Angela Putri; Sobari, Dolla (Program Studi Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Raden Fatah Palembang, 2023)
The research entitled Social Conflict in Alephia 2053 aims to find out the forms, causes and functions of social conflict in the Alephia 2053 film. This study uses a qualitative descriptive method with the type of research, namely literature review, data collection using the method of observing, recording and documentation, as well as data analysis using the method of content analysis and the contents of formal and informal data studies in the form of writing and tables. The results of this study know that in Alephia 2053 there are seven forms of realistic conflict in the form of disputes, hatred, anger, threats, prohibitions, suffering, and demonstrations, and there is one form of non-realistic conflict in the form of anxiety. The causes of the conflict found in the film Alephia 2053 are in the form of two factors, namely individual conflicts and conflicts of interest. The function of social conflicts are in the form of communication, generating solidarity, strengthening solidarity, and isolated communities playing a more active role.